The decline in forestry education enrollment – Some observations and opinions - Nyland, Ralph D. (Bosque (Valdivia), 2008)
Forestry enrollment in North America reached peak levels of the 1970’s, and colleges expanded their programs to fill a perceived need. Then numbers of college-age young people began to decline in the 80’s, as has an interest in forestry, leaving unfilled capacity in forestry colleges across the United States. Environmental science, biology, and policy studies seem more attractive to young people today. Yet broadening forestry curricula into natural resources management programs incorporating these fields of study, and substituting more policy and social sciences for some traditional forestry courses, has not reversed the trend. Neither has an easing of the requirements for graduation. Perhaps the slide in forestry school enrollment mirrors the declining reputation of forestry in general. A reversal may depend on a major shift in attitudes of society about the importance of forests and the people who manage them.